Implementasi Ekonomi Sirkular dalam Mendukung Pembangunan Berkelanjutan (Studi Literatur dengan Hasil Uji SEM-PLS) Implementation of Circular Economy in Supporting Sustainable Development (Literature Study with SEM-PLS Test Results) - Lumbanraja, Pretty Luci; Lumbanraja, Penny Charity (IDFoS Indonesia, 2024)
This research was conducted by analyzing the issue of implementing a green economy on Indonesia's income growth. The country's growth by implementing a green economic system is a solution to obtain the country's sustainable development goals. This research is exploratory in nature using descriptive and inferential analysis techniques. The data used in the range 2018-2022 (5 years) with SEM-PLS data analysis techniques. The research shows that there is a positive and significant influence between the circular economy on sustainable development with the results of p (0.000) <0.05 which gives a magnitude of influence of 0.881. The influence value of 0.881 means that the implementation of circular economy will make a considerable contribution in realizing sustainable development in Indonesia. Finally, from the empirical study conducted, it was found that sustainable development can be realized through waste management activities and using renewable energy sources.